2006
DOI: 10.1016/j.rmed.2005.09.027
|View full text |Cite
|
Sign up to set email alerts
|

High lung deposition of 99mTc-labeled ciclesonide administered via HFA-MDI to patients with asthma

Abstract: Inhalation of ciclesonide via HFA-MDI results in high pulmonary deposition, especially in the peripheral regions of the lung. High pulmonary deposition contributes to ciclesonide's ability to maintain lung function and control symptoms in patients with asthma. Deposition and activation of ciclesonide in the oropharynx is low, consistent with previous reports of low oropharyngeal deposition and a reduced incidence of local side effects in patients receiving ciclesonide therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 26 publications
9
94
0
2
Order By: Relevance
“…Similar results were obtained in asthmatic patients [43]. This minimises the oropharyngeal deposition of ciclesonide to ,39%, which compares favourably with other ICS [42,43].…”
Section: Formulation and Particle Sizesupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results were obtained in asthmatic patients [43]. This minimises the oropharyngeal deposition of ciclesonide to ,39%, which compares favourably with other ICS [42,43].…”
Section: Formulation and Particle Sizesupporting
confidence: 81%
“…Similar results were obtained in asthmatic patients [43]. This minimises the oropharyngeal deposition of ciclesonide to ,39%, which compares favourably with other ICS [42,43]. In a study performed in 18 healthy subjects, the oropharyngeal deposition of ciclesonide (800 mg ex-valve) and des-CIC was demonstrated to be less than half that of BUD (800 mg).…”
Section: Formulation and Particle Sizesupporting
confidence: 72%
“…19) The results of a radiolabeled deposition study showed that approximately 20% of the emitted dose from a nebulizer and approximately 50% of the emitted dose of ciclesonide from a MDI were deposited in the lungs. [20][21][22] In this study, we found that ICS delivery to the lung induces optimal efficacy with minimal toxicity in a model of BLM-induced injury and fibrosis in rats compared to conventional and long-acting steroids; this result was based on the pharmacokinetic profiles of the antedrug. For toxic indexes by BUD and DEX in rats, we used thymus and spleen weights as a marker of glucocorticoid activity.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the high pulmonary deposition of ciclesonide and the high affinity of the active metabolite for the glucocorticoid receptor potentially contribute to the improvements in lung function and asthma symptoms. [23,24] Approximately 52% of the ciclesonide dose, administered via HFA-MDI, is delivered to the lungs, with the highest deposition (55% of the deposited dose) in the peripheral regions of the lung. [23] In contrast, pulmonary deposition of budesonide via dry powder inhaler is lower (15%-28% of the administered dose) and deposition is localised primarily to the central region of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Approximately 52% of the ciclesonide dose, administered via HFA-MDI, is delivered to the lungs, with the highest deposition (55% of the deposited dose) in the peripheral regions of the lung. [23] In contrast, pulmonary deposition of budesonide via dry powder inhaler is lower (15%-28% of the administered dose) and deposition is localised primarily to the central region of the lung. [25,26] Furthermore, the active metabolite of ciclesonide (des-CIC) has a high relative glucocorticoid receptor affinity (1200 versus 900 for budesonide; dexamethasone reference is 100) and possesses substantial anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%